Frequency of Traumatic Dental Injuries to Anterior Teeth Among 7 to 14 Year-Old School Children - Qurat-Ul-Ain, Ali Shahid, Muhammad Afzal, Shehnoor Azhar, Hamna Khawaja, Muhammad Shairaz Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of traumatic injuries to the anterior teeth among 7 to 14 year-old school children. Design: It was a cross-sectional study. Study Settings: This study was done in 10 Government & Private High Schools of Lahore, Pakistan from November 2021 to April 2022. Material and Methods: There were a total of 2230 students between the ages of 7 and 14 participated in the study. Oral examinations and structured questionnaires were used to gather data, which included socioeconomic factors. Results: Total 11.3 percent of the permanent anterior teeth in the current study had TDI. It was found that there is a considerable gender difference in the incidence of dental trauma, with more boys than girls experiencing it. Fall-related injuries accounted for the majority of TDI cases (68.5 percent), then sports (11.2 percent). The permanent maxillary central incisors were frequently broken, with enamel-related fractures being the most frequently reported. The most frequent injury noted was an enamel fracture. Conclusion: Children of school age had a moderate prevalence of TDI, and it was advised that regular oral health education programmes about the causes and techniques of avoiding TDI be implemented. Keywords: Traumatic Dental Injuries, Prevalence, School Children, Anterior Teeth